2003
DOI: 10.1046/j.1365-2486.2003.00595.x
|View full text |Cite
|
Sign up to set email alerts
|

Methane (CH4) release from littoral wetlands of Boreal lakes during an extended flooding period

Abstract: Lake littoral zones have a transitional nature and dynamic conditions, which are reflected in their CH4 emissions. Thus, detailed studies are needed to assess the littoral CH4 emissions in a regional scale. In this study, CH4 fluxes were followed during the ice‐free seasons in 1998 and 1999 by using the static chamber method in the littoral zone of two lakes in Finland. An exceptionally high water level in 1998 caused an unusually long inundation in otherwise ephemerally flooded zone. The flooding was normal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
44
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 39 publications
(55 reference statements)
6
44
0
Order By: Relevance
“…Schuette and Klug (1995) reported that flowering individuals of Myriophyllum possess the ability to generate a pressure gradient during photosynthesis and have a great potential to transport gases by mass flow. CH 4 are effectively vented through plants, and by this transport mode, the proportion of CH 4 exposed to oxidation is smaller (Harden and Chanton, 1994;Kelker and Chanton, 1997;Juutinen et al, 2003).…”
Section: Article In Pressmentioning
confidence: 99%
“…Schuette and Klug (1995) reported that flowering individuals of Myriophyllum possess the ability to generate a pressure gradient during photosynthesis and have a great potential to transport gases by mass flow. CH 4 are effectively vented through plants, and by this transport mode, the proportion of CH 4 exposed to oxidation is smaller (Harden and Chanton, 1994;Kelker and Chanton, 1997;Juutinen et al, 2003).…”
Section: Article In Pressmentioning
confidence: 99%
“…Studies have demonstrated that littoral wetlands were 'hot spots' for CH 4 and N 2 O emissions (Juutinen et al 2003a;Wang et al 2006aWang et al , 2006bChen et al 2009). However, most of these studies were concentrated in boreal or cold regions Juutinen et al 2003aJuutinen et al , 2003bChen et al 2009Chen et al , 2011. Although lake areas in low latitudes are much smaller than in high latitudes, the estimated sediment GHG productions from low latitude lakes were substantially higher than boreal lakes (Marotta et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…(Juutinen et al, 2003;Wang et al, 2006;Bergstrom et al, 2007). In vegetated littoral areas, plants also play a very important role in the three aspects of CH 4 fluxes, i.e., providing the conduit for methane transportation, supplying substrates for methanogens through root exudation and delivering O 2 to oxidize methane (Dacey and Klug, 1979;Schü tz et al, 1991).…”
Section: Introductionmentioning
confidence: 99%